Planned Happenstance and Entrepreneurship Development: The Case of Japanese Undergraduate Students - Masaki Hosomi; Saddam Khalid; Tomoki Sekiguchi (Administrative Sciences, 2024)
This research aimed to investigate Japanese university students’ entrepreneurial development processes using the happenstance learning theory. The current research was an empirical study investigating the role of risk propensity, lifetime employment orientation, and entrepreneurship-related exploratory behaviour in developing the entrepreneurial intention of university students in Japan. Data were collected from 214 undergraduate students in Japan. The results demonstrated that the risk propensity characteristic of students influenced entrepreneurial intentions through entrepreneurship-related exploratory behaviour and lifetime employment orientation. The research also found that leadership experience moderated the relationship between risk propensity and entrepreneurship-related exploratory behaviour and the relationship between entrepreneurship-related exploratory behaviour and entrepreneurial intention. By applying the happenstance learning theory in an entrepreneurship study, the current research provides meaningful insights for research scholars, educators, and policymakers interested in the entrepreneurial intentions of students. This paper concludes with a discussion on the theoretical implications and future research directions.